Implementation of Virtual Laboratory Media to Learning Geometry in Mathematics Education Program of Universitas PGRI Semarang - Achmad Buchori; Agnita Siska Pramasdyahsari (International Journal of Research in Education, 2020)
Recently, the virtual laboratory is developing rapidly. One indicator is the number of Mathematics students both state and private Universities in Central Java who are looking for references related to practical geometry courses via online between lectures.  This raises concern as a lecturer in adding value to lectures, which are adapted to the 21st-century learning era today by creating virtual laboratories based on Virtual Reality. This research employed the ADDIE R & D model (Analysis, Design, Develop, Implementation and Evaluation) after the product is finished, the next step is implementing and marketing the product in state and private university in the region of Central Java and its surroundings. The consideration of creating the virtual lab is that the science virtual lab product has not been developed much in Indonesia, in fact, this lab is able to display virtual and augmented reality which can increase motivation and learning outcomes. Based on the validation of media and material experts on the virtual geometry lab product, the scores show that the virtual geometry lab product is very suitable for implementing and more than 90% of lecturers and students at the PGRI Semarang University are very happy to implement it.